2011
DOI: 10.4269/ajtmh.2011.10-0595
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Tegumentary Leishmaniasis in Brazil: Correlation between Level of Endemicity and Number of Cases of Mucosal Disease

Abstract: The purpose of this study was to establish a correlation between the endemic level of tegumentary leishmaniasis in different regions of Brazil during 2002–2009 and the number of cases of mucosal or mucocutaneous leishmaniasis. The proportion of mucosal leishmaniasis was inversely correlated with prevalence of infection. In areas with a lower infection prevalence, the proportion of mucosal leishmaniasis increased (P < 0.05). The hypothesis of an Amazonian origin and dissemination through human migration is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
9
0
4
Order By: Relevance
“…The Amazon forest seems to be the central distribution area with secondary spreads to the northeast, east and south. This would be consistent with the hypothesis of an Amazon origin of CL in Brazil, with later spread to other regions, most probably through human migrations [6]. However, we cannot exclude that sampling biases are responsible for the weak resolution of the strains in Population 3.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The Amazon forest seems to be the central distribution area with secondary spreads to the northeast, east and south. This would be consistent with the hypothesis of an Amazon origin of CL in Brazil, with later spread to other regions, most probably through human migrations [6]. However, we cannot exclude that sampling biases are responsible for the weak resolution of the strains in Population 3.…”
Section: Discussionsupporting
confidence: 89%
“…The disease is caused by six species of the subgenus L. ( Viannia ), L. (V.) braziliensis , L. (V.) guyanensis , L. (V.) shawi , L. (V.) lainsoni , L. (V.) naiffi and L. (V.) lindenbergi plus one species of the subgenus L. (Leishmania) , L. (L.) amazonensis . Around 6–7% of the CL patients will develop symptoms of MCL [6] mainly after infection with L. (V.) braziliensis and, to a lesser extent, also with L. (V.) guyanensis [7], [8]. So far, DL has been also mainly associated with L. (V.) braziliensis , and only sporadic cases with L. (V.) guyanensis [1].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the expansion of tegumentary leishmaniasis in Brazil is associated with migratory movements originating in the Amazon region. Dispersion of the diseases may have occurred following the return of the population to their regions of origin in the South and Southeast Brazil [ 53 , 54 ]. The return occurred in corridors with the population leaving the North, passing through the Mid-West and finally reaching the South region of the country [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dispersion of the diseases may have occurred following the return of the population to their regions of origin in the South and Southeast Brazil [ 53 , 54 ]. The return occurred in corridors with the population leaving the North, passing through the Mid-West and finally reaching the South region of the country [ 54 ]. Since then, there has been an increase both in the magnitude and in the geographical expansion of CML cases, with notifications in all regions of the country [ 34 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transformações ambientais e ecoepidemiológicas, aliadas a mudanças climáticas e desmatamento, assim como problemas econômicos com a consequente migração de pessoas infectadas das regiões endêmicas, contribuíram para a adaptação dos vetores e a expansão geográfica da doença com aparecimento de focos endêmicos urbanos e periurbanos. [3][4][5][6] Na atualidade, a leishmaniose cutânea vem sendo observada em todo o território brasileiro, com casos autóctones registrados em todas as unidades federadas, sendo encontrados com maior prevalência em populações mais pobres. 7 A partir de 2006, a leishmaniose cutânea foi incluída na lista de doenças endêmicas negligenciadas consideradas pelo Programa de Pesquisa e Desenvolvimento em Doenças Negligenciadas no Brasil, no âmbito do Ministério de Saúde e do Ministério de Ciência e Tecnologia.…”
Section: Introductionunclassified